Resolving Ambiguity in Kurdish Political Discourse: A Pragma-Theoretic Perspective - Bapir, Mohammed Hussein Ahmed Bapir (Sulaimani Journal for Humanities, 2025)
Political discourse, characterized by its intricate language and high potential for ambiguity, often results in challenges for the audience in the process of interpretation. In multilingual and culturally rich contexts like the Kurdistan Region, these challenges are even magnified. Hence, this study examines the role of pragmatics in resolving ambiguity in Kurdish political discourse. By analyzing the interplay of linguistic structures and pragmatic strategies, the research aims to explore how ambiguity can be mitigated to ensure effective communication. Via a theoretical lens, the study examines the applicability of pragmatic principles, in particular Grice’s cooperative maxims to interpret Kurdish political discourse. This analysis aims to unravel speakers’ intentions and their agenda in a given political context. The data analyzed is taken from selected political speeches delivered by representatives of the ruling parties in the Kurdistan Regional Government. The procedure involves analyzing selected extracts using cooperative maxims and discussing the results. The conclusions of the study ascertain the applicability of pragmatic principles to the interpretation of ambiguity in political discourse; and claim that the flouting of the maxim of manner, in the samples under study, outnumbers the other maxims for particular purposes. The study can be said to contribute to the broader field of discourse analysis and pragmatics, paving the way for future research in similar multilingual political contexts.
Keywords: ambiguity; interpretation; pragmatic principles; political discourse